Fly-away kite - Davis, Lee, 1941- (New York : DK Pub., 1997)
P.B. Bear and his friend lose their kite in a stream, but Delilah and her ducklings help them retrieve it.
Keywords: Teddy bears -- Fiction; Toys -- Fiction; Kites -- Fiction